DFT-based microkinetic modeling of ethanol dehydration in H-ZSM-5 - Alexopoulos, Konstantinos; John, Mathew; Van der Borght, Kristof; Galvita, Vladimir; Reyniers, Marie-Françoise; Marin, Guy B. (Journal of catalysis, 2016)
[Display omitted] •Experimentally validated microkinetic model for bio-ethanol dehydration.•Reaction path analysis not only based on free energy profiles.•Novel water- and ethanol-assisted mechanisms for ethene formation.•No kinetic inhibition of water on bio-ethanol dehydration.•Carbon number dependent activation entropies explain higher reactivity of butanol. A detailed reaction network has been constructed for ethanol dehydration in H-ZSM-5 using periodic density functional theory (DFT) calculations with dispersion corrections. Apart from the direct conversion of ethanol to diethyl ether or ethene, where novel mechanisms have been explored, the decomposition of diethyl ether to ethene has also been investigated. Thermodynamic and kinetic parameters were computed using statistical thermodynamics for all elementary steps. By coupling this microkinetic model to a plug-flow reactor model, macroscopic predictions of conversion and selectivity have been obtained at different operating conditions. The results of these simulations have been validated for H-ZSM-5 at different temperatures where experimental data are available. Both theory and experiment show an increase in ethene selectivity with increasing temperature and the experimental conversion agrees very well with the theoretical one. A reaction path analysis for ethanol dehydration in H-ZSM-5 shows that at temperatures above 500K ethene is mainly produced via the direct dehydration of ethanol, while at temperatures lower than 500K the reaction path via diethyl ether contributes significantly to ethene formation.